Enhancing students’ linguistic competence through Arabic conversational training: evidence from an Islamic boarding school context - Candrawati, Raniah Putri; Juliani, Juliani (UIR Press, 2026)
This study aims to examine the effectiveness of Arabic conversational training in enhancing students’ linguistic competence at Madani Ikhwanul Hasanah Islamic Boarding School, Deli Serdang, specifically at the MTs level. The research employed a quantitative approach with a one-group pre-test and post-test design. The sample consisted of 31 students selected from the boarding school population. Data were collected through speaking tests and analyzed using descriptive statistical techniques by comparing mean scores before and after the implementation of Arabic conversational training. The findings reveal a significant improvement in students’ linguistic competence after the intervention. The post-test results show higher mean scores compared to the pre-test, indicating that structured conversational practice effectively supports students’ ability to use Arabic more fluently and accurately in daily communication. This improvement suggests that consistent exposure to guided Arabic conversation contributes positively to developing students’ speaking proficiency in a real communicative context. The novelty of this study lies in its focus on the implementation of Arabic conversational training within a pesantren environment, where traditional language learning often emphasizes grammatical knowledge rather than active speaking practice. This research demonstrates that integrating communicative training into Islamic boarding school language instruction can bridge the gap between theoretical understanding and practical language use. The study implies that Arabic language teaching in Islamic boarding schools should shift toward more interactive and communicative approaches. Educators are encouraged to incorporate structured conversational activities to enhance students’ active language skills. This approach not only improves linguistic competence but also increases students’ confidence in using Arabic in real-life situations.